Multi-gene phylogeny and divergence estimations for Evaniidae (Hymenoptera) - Sharanowski, Barbara J.; Peixoto, Leanne; Dal Molin, Anamaria; Deans, Andrew R. (PeerJ (San Francisco, CA), 2019)
Ensign wasps (Hymenoptera: Evaniidae) develop as predators of cockroach eggs (Blattodea), have a wide distribution and exhibit numerous interesting biological phenomena. The taxonomy of this lineage has been the subject of several recent, intensive efforts, but the lineage lacked a robust phylogeny. In this paper we present a new phylogeny, based on increased taxonomic sampling and data from six molecular markers (mitochondrial 16S and COI , and nuclear markers 28S , RPS23 , CAD , and AM2 ), the latter used for the first time in phylogenetic reconstruction. Our intent is to provide a robust phylogeny that will stabilize and facilitate revision of the higher-level classification. We also show the continued utility of molecular motifs, especially the presence of an intron in the RPS23 fragments of certain taxa, to diagnose evaniid clades and assist with taxonomic classification. Furthermore, we estimate divergence times among evaniid lineages for the first time, using multiple fossil calibrations. Evaniidae radiated primarily in the Early Cretaceous (134.1–141.1 Mya), with and most extant genera diverging near the K-T boundary. The estimated phylogeny reveals a more robust topology than previous efforts, with the recovery of more monophyletic taxa and better higher-level resolution. The results facilitate a change in ensign wasp taxonomy, with Parevania , and Papatuka , syn. nov. becoming junior synonyms of Zeuxevania , and Acanthinevania , syn. nov. being designated as junior synonym of Szepligetella . We transfer 30 species to Zeuxevania , either reestablishing past combinations or as new combinations. We also transfer 20 species from Acanthinevania to Szepligetella as new combinations.